A RELIABLE RP-UPLC-TUV METHOD FOR SIMULTANEOUS ESTIMATION OF CLARITHROMYCIN, AMOXICILLIN, AND VONOPRAZAN IN CO-PACKED PHARMACEUTICAL DOSAGE FORMS: METHOD DEVELOPMENT AND VALIDATION WITH STABILITY INDICATING PROPERTIES - ANUSHA, K.; SOWJANYA, G. (International Journal of Applied Pharmaceutics, 2024)
Objective: The study aims to develop a reliable RP-UPLC-TUV method for simultaneous estimation of Clarithromycin, Amoxicillin, and Vonoprazan in bulk and combined dosage. Methods: A simple, specific, and reliable method for determining Clarithromycin, Amoxicillin, and Vonoprazan has been developed using the RP-UPLC method. In order to successfully separate Clarithromycin, Amoxicillin, and Vonoprazan, 1.0 µl of a 100 % level solution was injected into a Hibar C18 (100 x 2.1 mm and 2 µm) column. The mobile phase consisted of Ammonium Acetate and Acetonitrile in equal volumes, and the flow rate was kept at 0.3 ml/min while the detection wavelength was set to 210 nm. Both the column and the injection port were kept at a temperature of 30 °C at all times. Results: The retention time (RT) of Clarithromycin, Amoxicillin, and Vonoprazan was observed at 1.24 min, 0.97 min and 1.66 min, correspondingly with accepted system suitability. The linear responses were observed for Clarithromycin, Amoxicillin, and Vonoprazan in the range of 25 to 150 µg/ml, 25 to 150 µg/ml and 1 to 6 µg/ml, respectively. The LOD and LOQ values were calculated to 0.07 µg/ml and 0.22 µg/ml for Clarithromycin, 0.81 µg/ml and 2.45 µg/ml for Amoxicillin and 0.03 µg/ml and 0.09 µg/ml for Vonoprazan. The % RSD values of both precision were assessed in the range of 0.8-1.4. The mean recovery of Clarithromycin, Amoxicillin, and Vonoprazan was in the range of 99.66 %-100.88 %. The statistical analysis of the validation parameters confirmed that the approach was reliable in terms of its accuracy, sensitivity, and precision while also exhibiting a high degree of sensitivity. The study of analytes in a variety of stressful situations guarantees the stability of the substances, ensuring that they represent the method's stability indication. Conclusion: The newly established technique is quite effective in separating Clarithromycin, Amoxicillin, and Vonoprazan from one another. Also separated with excellent resolution were the degradation products that were formed as a result of the stress conditions. The study concluded that the developed method has considerable adoption in the pharmaceutical sector.